Writing about Writers: Mapping the Field and Moving Forward - Marsden, Stevie (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2018)
This article presents a literature review of existing academic, journalistic and non-fiction writing that has furthered the assessment of the writer and the occupation of writing in recent years. It is structured around four prominent themes that research about writers and writing commonly falls under: Being a Writer; Reputation, Fame and Hierarchies; Psychoanalyses of the Writer; and Economies of Writing. The final section of this article, Future Research, will propose research questions and methodological approaches which have, until now, remained largely absent from studies of the writer and writing life, and argues that these new areas of investigation are necessary to continue broadening the field of research about writing and furthering our understanding of the writer’s inspirations, motivations and work practices.